PROGRAM EMOTIONAL SPIRITUAL ACHIEVEMENT (ESA) DALAM MEMBENTUK POLA PIKIR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KOTA TANGERANG SELATAN - ety kurniyati; Abdul Basyit (Universitas Muhammadiyah Tangerang, 2021)
This study aims to describe the implementation of the Emotional Spiritual Achievement (ESA) Program in shaping students' mindsets towards Islamic Religious Education. The results of this study are expected to provide solutions for schools, in realizing a good education with good morals and good character. This research was conducted using qualitative methods with observation, interviews, and documentation techniques. The data that has been collected is analyzed through data reduction, data display, data validity and conclusions. This study shows that: 1) The Emotional Spiritual Achievement (ESA) program is very important to be followed and implemented by schools. 2) The role of Islamic Religious Education teachers is very important for the development of emotional and spiritual intelligence of students in schools. 3) The role of Islamic Religious Education teachers in developing the Emotional Spiritual Achievement (ESA) Program has been very good so that it can produce good output and character.